THE ACTIVE PHASE OF SEPARATISM IN CATALONIA - Мосора, М. А. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article deals with peculiarities of the intensification of separatism in Catalonia. The main causes of the Catalan separatist movement are revealed. The article recognizes the complicated nature of the origin of separatism as a phenomenon and proves the homogeneity of its basis in Europe. The author argues that the activation of secessionism in Catalonia in 2017 is an objective phenomenon. The author pays attention to the historical-cultural and economic factors of activation of the movement for the independence of the region. In the article the importance of internationalization of the discourse on the Catalan issue as a precedent in the field of ethno-national relations of the EU is substantiated. There has been identified the dual nature of influence on the movement of separation in the region, splitting into the economic factor and ethno-national identification on the basis of language. It is marked that the ideas of broad autonomy remain politically attractive in the region, since they recognize the urge of dual identity.